The Effect of Perceived Price, Product Quality and Location on Customer Satisfaction at Foresthree Coffe Kemang Pratama - Linca Natalia; Chatarina Yunita (Formosa Journal of Applied Sciences, 2023)
Research at Foresthree coffee Kemang pratama aims to find out how buyers at Foresthree coffee are influenced by price perceptions, product quality, location and customer satisfaction. This research was conducted using quantitative methods. In particular, the r-count was observed to be greater than the r-scale at a significance level of α 5% with valid results based on the adjusted R-Square value table of 0.831. Which shows that the influence of the three variables together has a fairly strong influence on customer satisfaction Forestgree Coffee Kemang Pratama. The influence contribution value of these three variables is 83.1% on customer satisfaction. This means that the perception of price and product quality and location presented by Foresthree Coffee Kemang Pratama has succeeded in attracting and creating a sense of satisfaction for their customers.